Structural characteristics and deformation behavior of porous titanium prepared by sintering - Anikeev, Sergey G.; Artyukhova, Nadezhda V.; Kaftaranova, Maria I.; Khodorenko, Valentina N.; Garin, Alexander S.; Marchenko, Ekaterina S. (Inorganic materials)
We have studied characteristic structural features of PTM-1 and PTS-1 titanium powders and related porous materials prepared by sintering the powders and determined quantitative characteristics of the pore system in the sintered materials. Macro- and microstructural features of the porous alloys have been shown to correlate with their deformation and strength parameters. The materials have been characterized by scanning electron microscopy, X-ray diffraction, and stereometric techniques, and their strength characteristics have been studied in compression tests. The porous material prepared by sintering the PTM-1 titanium powder has been found to have better principal strength and deformation characteristics owing to its lower porosity in comparison with the material obtained by sintering PTS-1 and to dispersion hardening by TiC particles in the structure formation process.